Variable Autosomal and X Divergence Near and Far from Genes Affects Estimates of Male Mutation Bias in Great Apes - Narang, Pooja (Genome Biol Evol, 2016)
Male mutation bias, when more mutations are passed on via the male germline than via the female germline, is observed across mammals. One common way to infer the magnitude of male mutation bias, α, is to compare levels of neutral sequence divergence between genomic regions that spend different amounts of time in the male and female germline. For great apes, including human, we show that estimates of divergence are reduced in putatively unconstrained regions near genes relative to unconstrained regions far from genes. Divergence increases with increasing distance from genes on both the X chromosome and autosomes, but increases faster on the X chromosome than autosomes. As a result, ratios of X/A divergence increase with increasing distance from genes and corresponding estimates of male mutation bias are significantly higher in intergenic regions near genes versus far from genes. Future studies in other species will need to carefully consider the effect that genomic location will have on estimates of male mutation bias.